2000
DOI: 10.1108/09526860010311035
|View full text |Cite
|
Sign up to set email alerts
|

Is the practice of psychological therapists evidence‐based?

Abstract: An interview-based survey of evidence-based practice (EBP) and the research, continuing professional development (CPD) and audit activity that support it was conducted in the North East of England amongst a representative sample of NHS clinical psychologists and counsellors (n = 30). It profiled their participation in EBP activities over the past year and their intentions for the next year. The findings suggest that the sample had used guidelines and protocols on 56 per cent of occasions, had on average drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
4
0
4
Order By: Relevance
“…Os itens 1,2,3,6,7,9,10,11,12,13,15,16,19,20,21,26, 28 e 30 permaneceram sem alterações na versão fi nal da escala.…”
Section: Tradução Da Fear Of Negative Evaluation Scale (Fne) -Silva Andunclassified
See 2 more Smart Citations
“…Os itens 1,2,3,6,7,9,10,11,12,13,15,16,19,20,21,26, 28 e 30 permaneceram sem alterações na versão fi nal da escala.…”
Section: Tradução Da Fear Of Negative Evaluation Scale (Fne) -Silva Andunclassified
“…Em sua construção, a FNE apresenta itens invertidos para o construto medido, sendo consideradas como respostas padrão "verdadeiro" nos itens 2,3,5,7,9,11,13,14,17,19,20,22,24,25,28, 29 e 30, e "falso" nos itens 1,4,6,8,10,12,15,16,18,21,23, 26 e 27.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Research has indicated that one of the factors influencing trainee decisions to publish research is the enthusiasm of the supervisor (Cooper & Turpin, 2007). Supervisor dissatisfaction may lead trainees to feel ambivalent about undertaking research and might contribute to a limited number of trainees undertaking and publishing research when they qualify (Milne, Keegan, Paxton, & Seth, 2000).…”
Section: Satisfaction Expectations and Role In Promotionmentioning
confidence: 99%
“…Os instrumentos psicométricos preenchem uma lacuna no campo de saúde mental -lacuna esta formada pela dificuldade de se estabelecer parâmetros objetivos e pela ausên-cia de marcadores biológicos para a identifi cação e avaliação de transtornos psiquiátricos 14 . Além disso, o aumento da valorização dos métodos baseados em evidências na área de saúde mental [15][16][17] , com maior importância atribuída aos delineamentos quantitativos em pesquisas nas áreas de psicologia e psiquiatria, também colabora para o crescimento do interesse por esses instrumentos objetivos.…”
unclassified